Biodiversity in remnants of natural mountain forests under conservation-oriented management - Horák, Jakub; Materna, Jan; Halda, Josef P; Mladenović, Strahinja; Bogusch, Petr; Pech, Pavel (Scientific reports, 2019)
The structure of forests is an important stabilizing factor regarding ongoing global climate and land use change. Biodiverse mountain forests with natural structure are one of the ecosystems most endangered by these problems. We focused on the mountain forest islands of European beech (Fagus sylvatica) and their role in the natural distribution of organisms. The study area was situated in the oldest Czech national park, Krkonoše (385 km2), which is the highest mountain ridge in the country. We studied multi-taxa (lichens, beetles and hymenopterans) responses to three hierarchical spatial levels of the environment: the topography was described by the elevation gradient; the patch structure was described by canopy openness, dead wood amounts, and Norway spruce (Picea abies) cover; and the tree level was described by species of the sampled tree and its diameter. Lichens preferred higher elevations, while insect groups responded conversely. Furthermore, insect groups were mainly influenced by the inner patch structure of beech islands. Lichens may be jeopardized due to the predicted future increase in temperatures, since they would need to shift toward higher altitudes. Insects may be mainly threatened in the future by land use changes (i.e., forest management) - as indicated by an interconnection of canopy openness and the amount of dead wood.
Keywords: brouci; Biodiversity; Lichens; Animals; lišejníky; zachování přírodních zdrojů; zvířata; Spatial Analysis; Coleoptera; Hymenoptera; prostorová analýza; lesy; Czech Republic; biodiverzita; Conservation of Natural Resources; Forests; Česká republika